2009
DOI: 10.1098/rspb.2009.2139
|View full text |Cite
|
Sign up to set email alerts
|

Explosive eversion and functional morphology of the duck penis supports sexual conflict in waterfowl genitalia

Abstract: Coevolution of male and female genitalia in waterfowl has been hypothesized to occur through sexual conflict. This hypothesis raises questions about the functional morphology of the waterfowl penis and the mechanics of copulation in waterfowl, which are poorly understood. We used high-speed video of phallus eversion and histology to describe for the first time the functional morphology of the avian penis. Eversion of the 20 cm muscovy duck penis is explosive, taking an average of 0.36 s, and achieving a maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
102
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(109 citation statements)
references
References 23 publications
7
102
0
Order By: Relevance
“…In describing the duck vagina, Brennan et al (2007) observed a spiral-shaped tube that was further characterized by blind pouches stemming from its distal half. When considering the waterfowl penis is corkscrewed with an opposite orientation to the spirals in the vagina (Brennan et al, 2010), the authors concluded that the anatomical incongruity between the phallus and vagina would be used by the female to impede the penetration of the penis during attempts at forced copulation.…”
Section: Anatomy and Histology Of The Uterus And Vaginamentioning
confidence: 99%
“…In describing the duck vagina, Brennan et al (2007) observed a spiral-shaped tube that was further characterized by blind pouches stemming from its distal half. When considering the waterfowl penis is corkscrewed with an opposite orientation to the spirals in the vagina (Brennan et al, 2010), the authors concluded that the anatomical incongruity between the phallus and vagina would be used by the female to impede the penetration of the penis during attempts at forced copulation.…”
Section: Anatomy and Histology Of The Uterus And Vaginamentioning
confidence: 99%
“…In waterfowl species that have evolved more elaborate phalluses, females have coevolved complex oviducts-i.e. blind pouches, and counter-sense spirals-that appear to function to selectively exclude the phallus [27]. Coevolutionary elaboration is positively associated with rate of forced extra-pair copulations (FEPCs) [26].…”
Section: Introductionmentioning
confidence: 99%
“…Coevolutionary elaboration is positively associated with rate of forced extra-pair copulations (FEPCs) [26]. Because female genital adaptations in waterfowl do not decrease the direct costs of male sexual coercion but appear to function solely in manipulating fertilization success ( [27], and discussion in §4), these structures could not have evolved by a narrow sense sexual conflict mechanism that excludes indirect effects. In addition, in waterfowl, females choose a mate and form a pair bond over a period of weeks prior to the breeding season when sexual coercion is non-existent [28].…”
Section: Introductionmentioning
confidence: 99%
“…Male genital morphology has been shown to be associated with sexual conflict during copulation in many taxa [14][15][16][17][18]. In North American natricine snakes, taxa with bilobed hemipenes have longer copulation durations than those with cylindrical hemipenes [34].…”
Section: Introductionmentioning
confidence: 99%
“…When males transfer other substances during copulation, for example a copulatory plug, conflict is likely to be more intense if these secretions negatively affect female fitness but positively affect male fitness [5,12,13]. Male genital morphology has been shown to be associated with sexual conflict during copulation in many taxa [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%